Thermal analysis of the photothermal effect based droplet microfluidic system. (31st August 2018) - Wang, Zhibin; Chen, Rong; Zhu, Xun; Liao, Qiang; Ye, Dingding; Zhang, Biao; Jiao, Long
Highlights: Photothermal effect based droplet microfluidic system is proposed for PCR applications. Thermal analysis of the proposed droplet microfluidics is performed. A linear relationship between the droplet temperature rise and laser power is found. Typical thermal cycle with quick response can be achieved. Abstract: In this work, the photothermal effect based droplet microfluidic system with the incorporation of the rail and anchor is proposed to complete the thermal cycle for the polymerase chain reaction (PCR) applications. Using the photothermal effect of the laser enables non-contact control of the droplet temperature with quick response, while the rail and anchor enables precise control of the droplet movement and easy focus on the droplet, respectively. With the proposed droplet microfluidic system, the thermal analysis towards the PCR application is then performed. It is found that when the Biot number of the droplet is less than or equal to 0.1, the uniform temperature distribution in the droplet can be ensured by selecting suitable carrying oil. A linear relationship between the droplet temperature rise and laser power is found, by which each characteristic temperature required in the PCR thermal cycle can be controlled by adjusting the laser power. The minimum temperature response time constant can be as low as about 0.175 s. The first thermal cycle with the consideration of the enzyme activation can be finished in 48.8 s and the following each thermal cycle can be completed in 28.6 s. The results obtained in this work have demonstrated the feasibility of the photothermal effect based droplet microfluidic system for the PCR applications.